Mechanics of composite materials : a unified micromechanical approach - Aboudi, Jacob, 1935- (Studies in applied mechanics, 1991)
In the last decade the author has been engaged in developing a micromechanical composite model based on the study of interacting periodic cells. In this two-phase model, the inclusion is assumed to occupy a single cell whereas the matrix material occupies several surrounding cells. A prominent feature of the micromechanical method of cells is the transition from a medium, with a periodic microstructure to an equivalent homogeneous continuum which effectively represents the composite material. Of great importance is the significant advantage of the cells model in its capability to analyze elastic as well as nonelastic constituents (e.g. viscoelastic, elastoplastic and nonlinear elastic), thus forming a unified approach in the prediction of the overall behaviour of composite material. This book deals almost exclusively with this unified theory and its various applications.